Vulnerabilidade à inundação por processos fluviais e alterações do uso e cobertura da terra na planície deltaica do rio Doce, Espírito Santo – Brasil - Santos, James Rafael Ulisses dos (2022)
Deltaic systems are dynamic environments that are at the interface between river and coastal systems, for this reason they undergo constant spatio-temporal morphodynamic changes, such as erosion and flooding, as well as changes in land use and cover, as a consequence of human activities. Therewith, the present work aimed to determine the vulnerability to flooding in the deltaic plain of the Rio Doce, through the integration of natural and anthropic fluvial conditions, using different methodological approaches. Therefore, it is worth considering that its evolution (deltaic plain) took place under higher sea level conditions than the current one, with the oceanic fringe potentially capable of serving as a barrier to recent changes in the intensification of oceanographic events. Thus, to achieve the proposed objectives, the methodological procedures were carried out based on bibliographic and documentary surveys, acquisition of cartographic data, study of the characteristics of the area and office work with the elaboration of thematic cartographic products, and application of multi-criteria methods (Boolean Logic and Hierarchical Analytical Process-AHP) for the production of flood models, using map algebra technique in a Geographic Information System-GIS environment. Where, the results, in turn, verified the changes that occur in terms of physical and socioeconomic aspects (land use and cover) over the years in the landscape of the deltaic plain of the Rio Doce. That said, with the integrated modeling of the variables: slope, geology, soils, geomorphology and land use and cover, it is possible to determine the vulnerability to flooding, where it was verified through the models, that the area presented a predominance for the classes high and very high, being validated by the extension of the flood pulses identified in the Landsat - 5 and 8 satellite images. The most vulnerable classes correspond to the flat and smooth wavy relief sectors, which comprise the deltaic subenvironments: fluviolagunar and fluviomarine plains, which, due to their morphological configuration, have a natural susceptibility to flooding events, especially when the main channel of the river overflows. Rio Doce, due to the extreme floods. Vulnerability with lower classes, on the other hand, was verified in the central sector, which is higher than the surroundings and covers the inter-distributary plain sub-environment. In addition, an analysis was carried out of the socio-environmental impacts that occurred in the medium-low river Doce on the construction of dams and the Samarco dam disaster in Mariana (MG), where changes in the fluvial and sociospatial morphological dynamics along the channel were verified. of the Rio Doce in the deltaic plain. Given the relative socio-environmental and economic importance of the deltaic plain of the Rio Doce and the results presented, this work can contribute to planning, management and decision-making in the deltaic environment.